Identification of Mangrove Health through Interpretation of Sentinel 2A Imagery and Aquatic Bioindicators in Tugu District, Semarang City - Anna, Alif Noor; Sari, Dewi Novita; Ariseno, Ilyas Ayub; Pramesti, Rizki Putri (Urecol Journal. Part E: Engineering, 2023)
Tugu Sub-district is one of the coastal areas in Semarang City that has a fairly extensive mangrove plant. These mangrove plants have a function to reduce and prevent sea water abrasion. In order for the function to run optimally, the health of mangrove plants needs to be monitored regularly. Research on mangrove plant health through sentinel 2A imagery has been conducted, but the results achieved are less than optimal. This is because mangrove health factors are not only seen from the vegetation index alone, but also the condition of the waters around mangroves. Seeing these shortcomings, researchers are trying to identify mangrove health based on the value of the vegetation index and its water bioindicator parameters. This study aims to identify mangrove health through sentinel 2A image interpretation and bioindicator parameters of mangrove waters. This study used a survey method accompanied by laboratory analysis. The results showed that sentinel imagery is effective enough to identify mangrove health with an accuracy value of 87.9%. Interpretation results showed mangroves with good health covering 37.03 ha, medium covering 36.42 ha, and low covering 189.14 ha. Based on aquatic bioindicator parameters (benthos and C-organic) shows that mangrove health conditions are still in fairly good condition. This is evidenced by the discovery of benthic diversity in the Tugu mangrove area which is dominated by the Gastropoda, Bivalvia, Echinoidhea, Malacostraca, and Scyphozoan classes. In addition, the value of C-Organic content is still quite high, which is 2.10 - 4.25%. Spatially high mangrove health is in the North Coastal Area of Tugu, moderate health is in the watershed area, and low mangrove health is in the pond area.